Syndrome of emotional burnout of teachers and its prevention - Zhakiyanova, J.G.; Musahanova, K. T (Ye.A.Buketov Karaganda State University Publishing house, 2018)
The article analyzes the problem of emotional burnout as one of the types of professional deformation of a teacher's personality. The stages and phases of the development of this deformation of personality are considered; symptoms of its manifestation; factors initiating this process; measures to prevent the development of this syndrome. The topicality and social significance of the chosen topic is the complex nature of the syndrome of emotional burnout, as well as the heterogeneity of the interpretation of its causes and manifestations, which require the search for research strategies and the creation of an appropriate psychological toolkit. The study of this phenomenon allows revealing the features of the burnout syndrome, to trace the mechanisms of the unfavorable impact of the profession on its development, to determine the factors causing its occurrence, to analyze the methods and methods of preventive work aimed at preventing and preventing possible violations in the cognitive, emotional and behavioral sphere. Identification of factors (internal and external), moderating the emergence and development of the syndrome of emotional burnout in teachers, is an important task currently facing researchers. Thus, the purpose of this article is a theoretical review of the available empirical studies devoted to the identification of external and internal factors moderating the emergence and development of the syndrome of emotional burnout in educators.
Оқытушылардың эмоционалдық күйзелу синдромы жəне оның алдын алу
Синдром эмоционального выгорания педагогов и его профилактика
Keywords: emotional burnout syndrome; stage; the phase of emotional burnout; symptoms of emotional burnout; prevention of emotional burnout syndrome